Ensino de Geografia para alunos com deficiência visual: problematização e possibilidades, o caso da Rede Municipal de Ensino de Santa Maria/RS - Pereira, Tassia Farencena (2022)
From the 1990s onwards, Brazil began to assume, in the educational field, a posture oriented towards the universalization of education, and to meet the aspirations of inclusion, the school had to restructure it self, overcoming the segregating educational culture, which created the school of the different, to build a school of differences. In this sense, the present research aimed to investigate, from the perception of Geography teachers from the municipal public network of Santa Maria, RS, the efficiency of the teaching and learning process of students with visual impairments. It was a qualitative research, which adopted as data collection a questionnaire with structured and semi-structured questions. Its methodological steps were based on the Content Analysis proposed by Bardin (2011). From the results obtained, it was verified that there have been significant advances in the theoretical field of educational policies at the federal, state and even municipal scale, with regard to guaranteeing the right to access to quality education for all citizens, especially for people with disabilities. However, we found that the theory does not always match reality, as the participating teachers showed through the speeches that they feel insecure, unprepared, and overwhelmed in the face of an inclusive school environment, these and other factors end up directly affecting the efficiency of the teaching process. Teaching and learning of students with visual impairments. Given the reality presented, improvements are necessary for schools to become spaces for all, so we consider the experiences and knowledge that teachers have as important strategies for removing obstacles that still bar the learning and participation of many students.